Exploring the Collaboration between Parents of Children with Learning Difficulties and Teachers in Inclusive Education - Grace, Pui; Dolly, Paul Carlo (2023)
Collaboration between parents of children with learning difficulties and teachers is a fundamental principle to bring inclusive education into practice. Parents and teachers are the main stakeholders with whom children with learning difficulties interact on a daily basis. This research was conducted to explore the existing collaboration between parents of children with learning difficulties and teachers in inclusive education. It is a qualitative study based on in-depth interviews with parents of children with learning difficulties and teachers selected through purposive sampling. Thematic analysis is used to construct themes from the collected data. The study found that informal meetings were more preferable than formal meetings. There are three types of collaboration between parents of children with learning difficulties and teachers: direct collaboration, indirect collaboration, and passive collaboration. Despite the importance of collaboration between parents and teachers, the decision to keep children with learning difficulties in mainstream classes still depends on their eligibility to be included.